2014
DOI: 10.7771/2157-9288.1074
|View full text |Cite
|
Sign up to set email alerts
|

High School Student Information Access and Engineering Design Performance

Abstract: Developing solutions to engineering design problems requires access to information. Research has shown that appropriately accessing and using information in the design process improves solution quality. This quasi-experimental study provides two groups of high school students with a design problem in a three hour design experience. One group has access to the internet while the other does not. Quality of design solution was measured and the two groups were compared. Solution quality did not change significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Evidence favoring this design‐science integration approach has been accumulating (e.g., Crismond, ; Fortus, Dershimer, Krajcik, Marx, & Mamlok‐Naaman, ; Hmelo, Holton, & Kolodner, ; Kolodner et al, ). However, it is also widely documented that students frequently show little attempt or have difficulties in making connections between the design challenges they are tackling and the underlying scientific concepts and processes (Carroll et al, ; Crismond, ; Mentzer, ; Roth, Tobin, & Ritchie, ). Many cross‐sectional studies have shown that students spent much less effort on gathering background information and analyzing their designs than experienced designers (Lammi & Gero, ; Lammi et al, ; Mentzer, Becker, & Sutton, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence favoring this design‐science integration approach has been accumulating (e.g., Crismond, ; Fortus, Dershimer, Krajcik, Marx, & Mamlok‐Naaman, ; Hmelo, Holton, & Kolodner, ; Kolodner et al, ). However, it is also widely documented that students frequently show little attempt or have difficulties in making connections between the design challenges they are tackling and the underlying scientific concepts and processes (Carroll et al, ; Crismond, ; Mentzer, ; Roth, Tobin, & Ritchie, ). Many cross‐sectional studies have shown that students spent much less effort on gathering background information and analyzing their designs than experienced designers (Lammi & Gero, ; Lammi et al, ; Mentzer, Becker, & Sutton, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many cross-sectional studies have shown that students spent much less effort on gathering background information and analyzing their designs than experienced designers (Lammi & Gero, 2011;Lammi et al, 2014;Mentzer, Becker, & Sutton, 2015). Even when they did, the information they gathered was often not related to science (Mentzer, 2014) and the knowledge they learned was highly contextualized and lacked connections to science concepts (Crismond, 2001). These novice behaviors are resistant to change even after substantial exposure to pre-college engineering learning opportunities (Kannengiesser, Gero, Wells, & Lammi, 2015;Lammi et al, 2014).…”
mentioning
confidence: 99%
“…A key difference between this administration of the playground design task and earlier studies using the playground task is that participants in this study were able to access information from the internet during our study (this approach is consistent with [27,28] ). As was in the case in previous studies using the playground task, our participants could also request specific information from the administrator (i.e.…”
Section: Discussionsupporting
confidence: 52%
“…They found that "on average, participants spent 38.8% of their total time accessing information" (p. 86), primarily from Internet-based sources, which was significantly more than college-level engineering students and expert engineers in previous studies. Another Mentzer (2014a) study compared two groups of high school students (30 students in each group) engaged in "a design problem in a three-hour design experience" in which "one group has access to the internet while the other does not" (p. 31). Mentzer found that "the most commonly requested piece of information related to cost of materials" (p. 31).…”
Section: Research Question 3: Impact Of Engineering Design On Studentsmentioning
confidence: 99%